IN-FLIGHT SIMULATION METHOD OF THE AIRCRAFT CARRIER LANDING - K. V. Zakharov; V. I. Zhelonkin; M. V. Zhelonkin; O. I. Tkachenko; A. A. Khokhlov (Научный вестник МГТУ ГА, 2016)
In-flight simulation method of the aircraft carrier landing was developed for the purpose of terms reduction and increase of flight training safety. The image of the simulated carrier and optical landing system are reproduced at the HUD. Flight training is conducted at some safety height. This training technique can be fulfilled without real carrier and its landing equipment. During the flight a pilot can fulfill simulation of the carrier landing unlimited times. Simulation of the carrier landing is continued up to moment when virtual hook touch the virtual deck.